2018
DOI: 10.1007/s10067-018-4063-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the different “patient global assessment” formulations on disease activity score by different indices in rheumatoid arthritis

Abstract: Patient global assessment (PGA) is included in almost all rheumatoid arthritis (RA) composite disease activity indices and definitions of remission. However, different PGA formulations exist and are used interchangeably in research and clinical practice. We investigated how five different PGA formulations used in four disease indices affect the remission rates. This was an ancillary analysis of data from a cross-sectional study in patients with RA. The data comprised the following: 28-joint counts, C-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In addition, ratings on this instrument are frequently responsible for patients not achieving defined remission states. Remission is also often influenced by which of the many versions of the PGA‐VAS is presented to patients . Few data exist regarding RA patients’ perspective regarding this instrument, but the Outcome Measures in Rheumatology (OMERACT) group has published valuable qualitative information about patients’ attitudes regarding the PGA‐VAS instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ratings on this instrument are frequently responsible for patients not achieving defined remission states. Remission is also often influenced by which of the many versions of the PGA‐VAS is presented to patients . Few data exist regarding RA patients’ perspective regarding this instrument, but the Outcome Measures in Rheumatology (OMERACT) group has published valuable qualitative information about patients’ attitudes regarding the PGA‐VAS instruments.…”
Section: Discussionmentioning
confidence: 99%
“…This potential confusion is concerning, given the prominent role the PGA‐VAS plays in RA clinical practice and research trials . Although the many different versions of the PGA‐VAS are often not scored similarly by RA patients, a low PGA score is mandated to reach either low disease activity or remission, as recommended in current disease management guidelines . In fact, numerous studies have shown that the PGA‐VAS score is often the sole reason that patients and research subjects do not meet criteria for remission, regardless of their literacy level .…”
Section: Introductionmentioning
confidence: 99%
“…Most patients are also unaware of the purpose of PGA, and have difficulties in completing the measurements reliably (Ferreira, de Wit, et al, 2019). With a quantitative study, we were able to confirm that the use of different versions of PGA introduces systematic errors in the rate of remission (Ferreira, Eugenio, et al, 2018).…”
Section: Inclusion Of Proms May Challenge the Treatment Target(s)mentioning
confidence: 66%
“…METEOR also incorporates data imported from other registries and the formulation of the PtGA question presented to patients is not exactly the same. Our previous research suggests that PtGA score varies by different formulations of the question. There was a significant amount of missing data (e.g., body mass index, smoking status, erosions) that could introduce some selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…PtGA is highly affected by comorbidities and by other musculoskeletal and psychological conditions (e.g., osteoarthritis, fibromyalgia, depression) that cannot be improved by therapies targeting the inflammatory process, which makes it inappropriate to guide the readjustment of such therapies . Additionally, concerns have been raised regarding the variety of formulations used to ask this question , which have been shown to influence remission rates by 4.7% to 6.3% . The patient's health literacy also affects the validity and reliability of PtGA: approximately 40% of patients find the concept of PtGA confusing and the instruments difficult to mark .…”
Section: Introductionmentioning
confidence: 99%